Trimeric Association of Hox and TALE Homeodomain Proteins Mediates Hoxb2 Hindbrain Enhancer Activity - Jacobs, Yakop (American Society for Microbiology, 1999)
Pbx/exd proteins modulate the DNA binding affinities and specificities of Hox proteins and contribute to the execution of Hox-dependent developmental programs in arthropods and vertebrates. Pbx proteins also stably heterodimerize and bind DNA with Meis and Pknox1-Prep1, additional members of the TALE (three-amino-acid loop extension) superclass of homeodomain proteins that function on common genetic pathways with a subset of Hox proteins. In this study, we demonstrated that Pbx and Meis bind DNA as heterotrimeric complexes with Hoxb1 on a genetically defined Hoxb2 enhancer, r4, that mediates the cross-regulatory transcriptional effects of Hoxb1 in vivo. The DNA binding specificity of the heterotrimeric complex for r4 is mediated by a Pbx-Hox site in conjunction with a distal Meis site, which we showed to be required for ternary complex formation and Meis-enhanced transcription. Formation of heterotrimeric complexes in which all three homeodomains bind their cognate DNA sites is topologically facilitated by the ability of Pbx and Meis to interact through their amino termini and bind DNA without stringent half-site orientation and spacing requirements. Furthermore, Meis site mutation in the Hoxb2 enhancer phenocopies Pbx-Hox site mutation to abrogate enhancer-directed expression of a reporter transgene in the murine embryonic hindbrain, demonstrating that DNA binding by all three proteins is required for trimer function in vivo. Our data provide in vitro and in vivo evidence for the combinatorial regulation of Hox and TALE protein functions that are mediated, in part, by their interdependent DNA binding activities as ternary complexes. As a consequence, Hoxb1 employs Pbx and Meis-related proteins, as a pair of essential cofactors in a higher-order molecular complex, to mediate its transcriptional effects on an endogenous Hox response element.